Biologic and genomic characterization of a novel virulent Aeromonas hydrophila phage phiA051, with high homology to prophages - Wang, Yuzhi; Tong, Guixiang; Jiang, Xinglong; Tu, Chuandeng; Cai, Hongjiao; Fang, Wenhong; Tan, Honglian; Weng, Qibiao; Wei, Xinxian; Lin, Mao (Frontiers in Veterinary Science, 2024)
Introduction Aeromonas hydrophila is particularly harmful to freshwater aquaculture, and the search for phage is an effective biological control method, but reports of possible temperate phages and their mutants are rare in this field. In this study, a virulent phage highly homologous to prophage in the genomes of A. hydrophila was collected and preliminary biological characterization was carried out to understand its nature. Materials and methods Water samples taken from eel ponds in Fujian, China were combined with the strain. Spot test method and double-layer agar plate assay was used for confirmation and purification. Phage virions were observed using transmission electron microscope. A total of 68 strains of Aeromonas spp. were used to determine the host range. MOI groups of 1,000, 100, 10, 1, 0.1, 0.01, 0.001, 0.0001, 0.00001 were prepared to detect the optimal MOI. The conditions of thermal stability assay were set as 30, 40, 50, 60, 70 and 80°C for 1 h, respectively, and conditions of acid and alkali stability assay were set as 2.0, 4.0, 6.0, 8.0, 10.0 and 12.0 of pH. MOI of 0.01 and 0.1, respectively, are set to determine the inhibitory capacity of phage. Results A novel virulent A. hydrophila phage designated phiA051 has been isolated from aquaculture water. Electron microscopic observation showed that the phage phiA051 was composed of an icosahedral capsid. The phage phiA051 possesses an optimal multiplicity of infection (MOI) of 0.01, and its burst size was 108 PFU/cell. The phage maintained a high viability at temperatures of 30–50°C or pH 6.0–10.0 for 1 h. Phage phiA051 has certain potentials in rapidly inhibiting the spread of pathogen early in the outbreak, and it has a linear dsDNA with GC content of 60.55% and a total length of 32,212 bp, including 46 ORFs. Discussion The phage phiA051 behaved as a virulent phage. However, the BLASTN result showed that 23 of the top 25 hits were genomes of Aeromonas strains. It was suggested that phiA051 was probably derived from some prophage in the chromosome of Aeromonas. Further investigation of the mechanism how phage phiA051 transforms from a temperate phage to a virulent phage will provide a unique perspective and idea to explore the potential of prophages.